Iron metabolism mediates microglia susceptibility in ferroptosis - Jiao, Lingling; Li, Xiaolan; Luo, Yuxiang; Wei, Junfen; Ding, Xulong; Xiong, Huan; Liu, Xuesong; Lei, Peng (Frontiers in Cellular Neuroscience, 2022)
Ferroptosis is implicated in a range of brain disorders, but it is unknown whether neurons or glia in the brain are particularly effected. Here, we report that primary astrocytes (PA), microglia (PM), and neurons (PN) varied in their sensitivity to ferroptosis. Specifically, PM were the most sensitive to ferroptosis, while neurons were relatively insensitive. In contrast, PN and PM were equally susceptible to apoptosis, with PA being less affected, whereas all three cell types were similarly susceptible to autophagic cell death. And the tri-culture system containing PA, PM, and PN was more resistant to ferroptosis than that of monoculture. These results demonstrated that brain cells exhibit different sensitivity under ferroptosis stress and the difference may be explained by the differentially regulated iron metabolism and the ability to handle iron. Continued elucidation of the cell death patterns of neurons and glia will provide a theoretical basis for related strategies to inhibit the death of brain cells.